1991
DOI: 10.3143/geriatrics.28.358
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Ventricle Dilation and Clinical Findings between the Early- and Late-Onset Subtypes of Alzheimer's Dementia.

Abstract: Attempts to vanquish Alzheimer's disease intensity, take new paths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…45,46 However, amyloid β-injected rabbits did not demonstrate these volumetric changes within 25 days, 34 but after 60 days, these rabbits demonstrated significant volumetric changes in the temporal lobe and lateral ventricles. 37 In this study, Al-M-treated aged New Zealand rabbit showed significant volumetric changes in the 47 The robust studies and findings in humans have demonstrated temporal lobe atrophy and ventricular dilatation, [13][14][15][19][20][21][22][23][24][25][26][27][28][29][30] but they have failed to streamline substantial therapeutic strategies to either stop or slow down the progression of AD. Our recent studies on animal models have highlighted the role of animal models and molecular-level studies in AD pathology.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…45,46 However, amyloid β-injected rabbits did not demonstrate these volumetric changes within 25 days, 34 but after 60 days, these rabbits demonstrated significant volumetric changes in the temporal lobe and lateral ventricles. 37 In this study, Al-M-treated aged New Zealand rabbit showed significant volumetric changes in the 47 The robust studies and findings in humans have demonstrated temporal lobe atrophy and ventricular dilatation, [13][14][15][19][20][21][22][23][24][25][26][27][28][29][30] but they have failed to streamline substantial therapeutic strategies to either stop or slow down the progression of AD. Our recent studies on animal models have highlighted the role of animal models and molecular-level studies in AD pathology.…”
Section: Discussionmentioning
confidence: 98%
“…The robust studies and findings in humans have demonstrated temporal lobe atrophy and ventricular dilatation, , but they have failed to streamline substantial therapeutic strategies to either stop or slow down the progression of AD. Our recent studies on animal models have highlighted the role of animal models and molecular‐level studies in AD pathology .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early brain volume involution in neurodegenerative diseases, as a measure of brain atrophy, can be considered as a potential predictor for cognitive impairment. Moreover, on the basis of the third ventricle or midbrain area ( 14 , 15 ) differentiation between different forms of dementia are made.…”
Section: Introductionmentioning
confidence: 99%